SCALING RETAIL BUSINESS: GROWTH STRATEGIES FOR RETAIL CHAINS - Perekrest, Serhii (Global Prosperity, 2025)
This article analyzes modern approaches to employee motivation in the retail sector, which is rapidly evolving due to economic shifts, digitalization, changing consumer behavior, and labor market competition. The topic is especially relevant amid post-pandemic recovery, hybrid work models, and rising employee expectations for sustainability and emotional well-being. The evolution of motivation systems is explored, from traditional financial incentives to integrated strategies emphasizing engagement, emotional intelligence, recognition culture, and internal communication. The study is grounded in classical theories by Maslow and Herzberg and modern concepts by D. Pink, who highlights autonomy, mastery, and purpose as key non-material drivers. A comparison is made between KPI-driven models and engagement-focused approaches. The former ensures measurable performance, while the latter fosters loyalty and long-term productivity. Research by McKinsey (2022) and Gallup (2022) shows that organizations prioritizing engagement report higher productivity and lower turnover. The article advocates for a hybrid motivation model combining financial and non-financial tools: KPI bonuses, recognition programs, training, onboarding with mentoring, and employee satisfaction surveys. A proposed model includes four components: performance (KPI), engagement (loyalty, internal participation), development (education, coaching), and recognition (awards, internal PR), aligning with Deloitte’s 2021 HR findings. Real-world cases from Ukrainian retail chains (ATB, EVA, Silpo) illustrate how such strategies reduce turnover and improve service quality, validating the shift toward multidimensional motivation systems.Ultimately, the article highlights the strategic value of balancing performance and engagement to ensure sustainable growth in the retail industry.